Differential photoacoustic spectroscopic (DPAS)-based technique for PM optical absorption measurements in the presence of light absorbing gaseous species. Issue 12 (2nd December 2017) - Yu, Zhenhong; Assif, James; Magoon, Gregory; Kebabian, Paul; Brown, William; Rundgren, William; Peck, Jay; Miake-Lye, Richard; Liscinsky, David; True, Bruce
ABSTRACT: In this study, we developed an optical monitor to measure light absorption from particulate matter (PM) at 532 nm using a differential photoacoustic absorption spectroscopic (DPAS) technique. The dual-cell system is capable of measuring the photoacoustic signals due to light absorption of total PM and gaseous samples and that of gaseous samples, separately. The resulting differential photoacoustic signal can be used to determine the light absorption purely from the PM species. This measurement method eliminates the interferences from the light-absorbing gaseous species as well as the surrounding low-frequency background acoustic noises. Photoacoustic signals of the DPAS monitor were calibrated with the NO2 gas standards, varying from 100 to 250 parts per billion (ppb). Based on an Allan analysis, a detection sensitivity (2σ) of 0.68 Mm −1 can be achieved in 100 s data acquisition. Using the Jet Burner Test Stand (JBTS) facility at the United Technologies Research Center (UTRC), we measured light absorption by the soot emissions from a representative high-temperature and high-pressure test combustor for aircraft auxiliary power units (APU). The DPAS measurement results at 532 nm, under the high gaseous NO2 conditions, were then compared to the determination of soot mass concentrations from a commercial AVL Micro Soot Sensor (MSS). An excellent linear correlation between the measurements from two instruments was observed. The mass absorption coefficient (MAC) of the soot using the two data sets was 7.4 ± 1.3 m 2 g −1, in good agreement with the previously reported 8.1 ± 1.7 m 2 g −1 and the expected value of 7.6 ± 0.6 m 2 g −1 . Copyright © 2017 American Association for Aerosol Research